The Indian and Polish transnational organisational fields - Lacroix, T (International Migration Institute, 2011)
Although the cross-border engagements of immigrants have received an increasing attention since the 1990s, the role of migrant organisations in this process has spurred comparatively little interest. As a consequence, efforts to conceptualise migrant organising in the transnational sphere have been relatively scarce. This paper seeks to contribute to this effort by proposing a more systematic definition and use of the concept of transnational organisational fields. This endeavour is illustrated by two case studies based on research carried out within the TRAMO project (Diffusion and Contexts of Transational Migrant Organisations): Indian and Polish organisations in the UK. The intent is to show that much can be gained by adopting a bird’s-eye view on the networks that bind together migrant organisations within and outside the country of settlement. The two case studies display two opposite forms of structuring. In the Polish case, the formation of the field was managed by a central institution (the Polish government in exile) while, in the Indian case, there was a decentralised process. These discrepancies have consequences on the shape and contents of cross-border activities of migrant organisations.